2019
DOI: 10.1111/cyt.12716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellular adequacy in endometrial liquid‐based cytology

Abstract: Objective This study evaluated cellular adequacy in endometrial liquid‐based cytology (LBC) specimens. Methods In total, 1267 cases were obtained and the rate of unsatisfactory specimen and diagnostic accuracy for malignancy were assessed. If ≥10 cellular clusters composed of ≤30 endometrial cells were found per specimen, then the sample was provisionally considered adequate. Results The unsatisfactory rate (with fewer than 10 clusters) was 15.4%. Diagnostic accuracy in specimens with ≥10 clusters was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Regarding the number of clusters, it has been reported that 10 or more clusters comprising 30 or more cells collected by brushing and prepared by LBC are sufficient to make a cytologic diagnosis [16]. In our study, the numbers of clusters converted to that per preparation using a smear area of 133 mm 2 were 514 in G1 and 140 in G3 in LBC, and 55 and 50 in CP, respectively, showing that a sufficient amount to make a diagnosis was collected by both procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the number of clusters, it has been reported that 10 or more clusters comprising 30 or more cells collected by brushing and prepared by LBC are sufficient to make a cytologic diagnosis [16]. In our study, the numbers of clusters converted to that per preparation using a smear area of 133 mm 2 were 514 in G1 and 140 in G3 in LBC, and 55 and 50 in CP, respectively, showing that a sufficient amount to make a diagnosis was collected by both procedures.…”
Section: Discussionmentioning
confidence: 99%
“…For staining of the cytology preparations, Papanicolaou staining was used. Cell clusters were defined as those comprising 30 or more cells with a longitudinal diameter of the cluster within 300 μm [16]. This study was approved by the Ethics Committee of Hirosaki University Graduate School of Medicine (No.…”
Section: Methodsmentioning
confidence: 99%
“…The cytological specimens were stained by the Papanicolaou method. Cell clusters were defined as aggregates 300 μm or less in longitudinal dimension consisting of 30 or more cells [21]. This study was approved by the Ethics Committee of Hirosaki University Graduate School of Medicine (No.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess adequacy of endometrial specimen, the evaluation specimen cellularity (numerical criterion) is among the most important issues. The study conducted by Nimura et al (19) demonstrated the ≥10 clusters with ≥30 endometrial cells per cluster could be used as a specimen adequacy criterion for endometrial liquid based cytology in non-menopausal patients, while presence of 5 or more cell clusters was satisfactory in post-menopausal patients.…”
Section: Methodsmentioning
confidence: 99%